ANALYSIS OF ORGANIZATIONAL COMMITMENTS AND WORK SATISFACTION TURNOVER INTENTION GARMENT COMPANY - Anggih Perian Guswan Putra; Irvan Arif Kurniawan; Agus Iwan Mulyanto; Erialdy . (UNIVERSITAS ISLAM SYEKH YUSUF, 2020)
This research was conducted to analyze and investigate the impact of organizational commitment and job satisfaction on the intention to move perceived by the operator employees of one of the Garment Companies. Data is collected through surveys and library studies. The questionnaires were sent to respondents returned resulting in a response rate of 98%. From correlation and regression analysis, this study found that the correlation and impact of turnover intention have been supported. Of the four hypotheses that have been tested in this study, all hypotheses are supported. The results showed that the existence of organizational commitment and job satisfaction was negatively and significantly related to turnover intention and negatively affected the company.